Cluster – As a Business Entity (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article examines the improvement of ownership and intellectual property relations of new farms, the direction from the material and legal basis of liberalization to modernization and diversification of economic reforms carried out in today's global and difficult conditions will be aimed at forming a new way of life in the regions and territories of a diversified and multidisciplinary sector of the economy.